The protective effect of aqueous extracts of roselle (Hibiscus sabdariffa L. UKMR-2) against red blood cell membrane oxidative stress in rats with streptozotocin-induced diabetes - Mohamed, Jamaludin (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2013)
OBJECTIVES: The aim of this study was to investigate the protective effects of aqueous extracts of roselle (Hibiscus sabdariffa L. UKMR-2) against red blood cell (RBC) membrane oxidative stress in rats with streptozotocin-induced diabetes. METHODS: Forty male Sprague-Dawley rats weighing 230-250 g were randomly divided into four groups (n = 10 rats each): control group (N), roselle-treated control group, diabetic group, and roselle-treated diabetic group. Roselle was administered by force-feeding with aqueous extracts of roselle (100 mg/kg body weight) for 28 days. RESULTS: The results demonstrated that the malondialdehyde levels of the red blood cell membranes in the diabetic group were significantly higher than the levels in the roselle-treated control and roselle-treated diabetic groups. The protein carbonyl level was significantly higher in the roselle-treated diabetic group than in the roselle-treated control group but lower than that in the diabetic group. A significant increase in the red blood cell membrane superoxide dismutase enzyme was found in roselle-treated diabetic rats compared with roselle-treated control rats and diabetic rats. The total protein level of the red blood cell membrane, osmotic fragility, and red blood cell morphology were maintained. CONCLUSION: The present study demonstrates that aqueous extracts of roselle possess a protective effect against red blood cell membrane oxidative stress in rats with streptozotocin-induced diabetes. These data suggest that roselle can be used as a natural antioxidative supplement in the prevention of oxidative damage in diabetic patients.